Analisis Perbandingan Ruang dan Waktu pada Algoritma Sorting Menggunakan Bahasa Pemrograman Python - Yayan Heryanto; F Fauziah; Trinugi Wira Harjanti (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
The role of algorithms in software or programming is very important, so understanding the basic concepts of these algorithms is essential. A lot of programming logic has been made, and in sorting data, insertion sort, quick sort, bubble sort, selection sort, and merge sort algorithms have been used. If you get random data with values of 200, 300, 400, and 500, using the manual method will take a long time, so the five algorithms are used with the Python programming language to sort random data of integer data type. The time required and the size of memory used in each algorithm will be examined during the sorting process. An effective algorithm is one that has a short processing time and uses little memory, so that in this journal, the results for the time efficiency of the Quick Sort algorithm are superior, namely with inputs of 200, 300, 400, and 500, it takes 0.001 seconds, 0.001 seconds, 0.003 seconds, and for memory usage, the Bubble Sort algorithm is superior because it only requires a small amount of memory.